Neuronal Growth and Behavioral Alterations in Mice Deficient for the Psychiatric Disease-Associated Negr1 Gene - Singh, Katyayani; Loreth, Desirée; Pöttker, Bruno; Hefti, Kyra; Innos, Jürgen; Schwald, Kathrin; Hengstler, Heidi; Menzel, Lutz; Sommer, Clemens J.; Radyushkin, Konstantin; Kretz, Oliver; Philips, Mari-Anne; et al. (Frontiers in Molecular Neuroscience, 2018)
Neuronal growth regulator 1 (NEGR1), a member of the immunoglobulin superfamily cell adhesion molecule subgroup IgLON, has been implicated in neuronal growth and connectivity. In addition, genetic variants in or near the NEGR1 locus have been associated with obesity and more recently with learning difficulties, intellectual disability and psychiatric disorders. However, experimental evidence is lacking to support a possible link between NEGR1, neuronal growth and behavioral abnormalities. Initial expression analysis of NEGR1 mRNA in C57Bl/6 wildtype (WT) mice by in situ hybridization demonstrated marked expression in the entorhinal cortex and dentate granule cells. In co-cultures of cortical neurons and NSC-34 cells overexpressing NEGR1, neurite growth of cortical neurons was enhanced and distal axons occupied an increased area of cells overexpressing NEGR1. Conversely, in organotypic slice co-cultures, Negr1-knockout (KO) hippocampus was less permissive for axons grown from entorhinal cortex of β-actin-EGFP mice compared to WT hippocampus. Neuroanatomical analysis revealed abnormalities of entorhinal cortex axons in the hippocampal dentate gyrus of Negr1-KO mice including increased numbers of axonal projections to the hilus. Neurotransmitter receptor ligand binding densities, a proxy of functional neurotransmitter receptor abundance, did not show differences in the dentate gyrus of Negr1-KO mice but altered ligand binding densities to NMDA receptor and muscarinic acetylcholine receptors M1 and M2 were found in CA1 and CA3. Activity behavior, anxiety-like behavior and sensorimotor gating were not different between genotypes. However, Negr1-KO mice exhibited impaired social behavior compared to WT littermates. Moreover, Negr1-KO mice showed reversal learning deficits in the Morris water maze and increased susceptibility to pentylenetetrazol (PTZ)-induced seizures. Thus, our results from neuronal growth assays, neuroanatomical analyses and behavioral assessments provide first evidence that deficiency of the psychiatric disease-associated Negr1 gene may affect neuronal growth and behavior. These findings might be relevant to further evaluate the role of NEGR1 in cognitive and psychiatric disorders.